Correlation Between N95 Extended Use and Reuse and Fit Failure in an Emergency Department - Degesys, Nida F. (JAMA, 2020)
This cross-sectional study examines prevalence of fit test failure of 2 types of N95 mask (dome-shaped and duckbill) during extended use or reuse among health care workers over 2 days in April 2020 in the UCSF emergency department.